A Fast Solver for an H1 Regularized PDE-Constrained Optimization Problem. (15th January 2016) - Barker, Andrew T.; Rees, Tyrone; Stoll, Martin
Abstract: In this paper we consider PDE-constrained optimization problems which incorporate an H1 regularization control term. We focus on a time-dependent PDE, and consider both distributed and boundary control. The problems we consider include bound constraints on the state, and we use a Moreau-Yosida penalty function to handle this. We propose Krylov solvers and Schur complement preconditioning strategies for the different problems and illustrate their performance with numerical examples.